Medium-term dynamics of tree species composition in response to silvicultural intervention intensities in a tropical rain forest. (November 2015) - de Avila, Angela Luciana; Ruschel, Ademir Roberto; de Carvalho, João Olegário Pereira; Mazzei, Lucas; Silva, José Natalino Macedo; Lopes, José do Carmo; Araujo, Maristela Machado; Dormann, Carsten F.; Bauhus, Jürgen
Abstract: Managed forests are important landscape components in tropical regions and may contribute to biodiversity conservation. Yet, managing tropical forests sustainably requires an understanding of ecosystem responses to silvicultural interventions. We investigated how silvicultural intervention intensity affects tree species composition and diversity over 30 years in the Brazilian Amazon by comparing them to pre-logging conditions and to an unlogged control. The interventions comprised logging in 1982 and thinning in 1993–1994 and ranged in intensity from 19 to 53% reduction in the original basal area (BA). Trees with a diameter at breast height (DBH) ≥ 5 cm were measured on eight occasions in 41 permanent sample plots of 0.25 ha each. Silvicultural intervention intensity influenced both tree species composition and its trajectory within 30 years. In contrast, tree species diversity was not impaired. High intervention intensities (with BA reduction > 6.6 m 2  ha − 1 ) had a substantial influence on the community of trees (DBH ≥ 10 cm), which did not show signs of return to pre-logging species composition. The reduction of BA through harvesting damage and thinning had a stronger effect on species composition than logging of mature trees itself. Thus, damage should be kept to a minimal level and strong thinning interventions should be avoided. This may enhance ecosystem recovery and maintenance of biodiversity at other trophic levels. Since current permitted harvesting intensities in the Brazilian Amazon are lower than the lowest intensity examined in our study, legal harvesting practices are unlikely to cause substantial, long-term changes in tree species composition. Highlights: Unique long-term experiment on management effects on forest ecosystem recovery Tree species dynamics documented through 8 repeated inventories over 31 years Harvesting damage and thinning had a greater impact on composition than logging. Composition did not show signs of recovery after basal area reduction of > 6.6 m 2  ha − 1 .